2020
DOI: 10.4103/jehp.jehp_493_20
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of Iran health system reform plan

Abstract: INTRODUCTION: Iran's Health System Reform Plan (HSRP) were initiated in public and hospitals affiliated to Medical Sciences Universities in June 2015. The purpose of the present paper is to provide a critical analyse of the HSRP and its outcomes. METHODS: The study was carried out as a review critical analyse in 2019. The pertinent articles were searched for in Science Direct, PubMed, Ovid, and Google Scholar using keywords “health sector,” “reform plan,” “health system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This can reduce the production of bulky stools, making it easier to pass through the gut. However, if this does not work, surgery may be needed to repair or replace the damaged part of the bowel [4]. Complete obstruction is a medical emergency.…”
Section: How Is Intestinal Obstruction Treated?mentioning
confidence: 99%
See 1 more Smart Citation
“…This can reduce the production of bulky stools, making it easier to pass through the gut. However, if this does not work, surgery may be needed to repair or replace the damaged part of the bowel [4]. Complete obstruction is a medical emergency.…”
Section: How Is Intestinal Obstruction Treated?mentioning
confidence: 99%
“…Several therapeutic strategies have been tested to reduce POI. Sham feeding, for example gummy candy has been reported to decrease POI [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Using one-way analysis of variance and meta-analysis were analyzed. The subjects included 1,775 patients with coronary artery disease, including 206 deaths from Jinni Nathan Hospital in Wuhan, as well as 113 and 285 other patients with the disease from Renin Hospital in Wuhan University and Shenzhen Hospital, respectively [16][17][18]. The results showed that the distribution of blood groups in Wuhan is as follows: 31% had blood type A, 24% had blood type B, 9% had blood type AB, and 34% had blood type O.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a comparison of the world aging distribution map in 2015 and 2050, we have found that Iran will change from a young country to a definitive aging country in just the next 30 years [1][2][3]. In other words, while in 2020, the elderly over 60 years old constituted only 10% of the population of Iran, but as a result of the rapid phenomenon of population aging, in 2050 about 33% of the total population of the country will be elderly [4].…”
Section: Introductionmentioning
confidence: 99%